Small Business Management / Third Edition - Burns Paul; Dewhurst Jim; Macmillan (1993)
A comprehensive guide to the management of small and medium sized enterprises (SMEs), from conception and efficient operations through to the management growth. Preface, Introduction, Setting Up, The Genesis of a Business, Business and the Law, Business Taxation, Business Basics, Marketing, Understanding Accounts, Contribution and Break-Even Analysis, Planning, The Business Plan, Financial Planning and Budgeting, Finance, Bank Finance, Financial and Other Services for SMEs, Risk Capital, Control, Accounting Systems, Costing Products, Using Budgets, Analyzing Accounts, The Management of Money, Inventory Management, Decision Making, Capital Investment Appraisal, The Growing Business, Managing Growth, The European Dimension, Relative Performance of SMEs, The Future for SMEs, Select Bibliography, Index.